Nature Tourism, Conservation, and Development in KwaZulu-Natal, South Africa - Aylward, Bruce; Lutz, Ernst (Washington, DC: World Bank, 2013)
The book provides an evaluation of, and policy advice on key environmental, social, and economic issues concerning the development of nature tourism. Using KwaZulu-Natal in South Africa as a case study, it highlights both the benefits, and trade-offs I promoting, an managing sustainable nature-tourism development, and it assesses how policy can enhance nature tourism's contribution to economic growth, poverty reduction, and conservation. The book's contributors explore three key issues. First, they consider the importance of moving beyond development of a wildlife industry, to the creation of a true nature tourism economy, that supports biodiversity conservation. Second, they explore the role of the private sector in contributing to equitable development, and job creation, while generating conservation finance. Third, they consider alternative pricing, and other market mechanisms that can help make nature tourism more viable, and growth-oriented. Ultimately, the authors argue, economic development, equity, and conservation objectives can be balanced.